1992
DOI: 10.1080/03601239209372790
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability to rats and toxicity in mice of carbofurah residues bound to faba beans

Abstract: 14C-carbofuran penetrated readily into seeds of Vicia faba and the rate of penetration was found to be dose dependent. The percentage of bound residues was generally low and did not exceed 3% of the applied dose. When the bound residues were fed to rats 46% of the radioactivity was eliminated via CO2 and urine, while tissues contained 25%. Carbofuran phenol and 3-hydroxy carbofuran represented the main metabolites in the urine. These data indicate that bean-bound carbofuran residues are highly bioavailable to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…Similar results were reported from studies on the bioavailability of soybean bound residues of pirimifos methyl (40) , chloropyrofos (41) , dichlorovos (42) and fenitrothion (43) . Also, the data obtained are in line with many other studies which indicate a moderate to high bioavailability of grains bound 14 C-pesticide residues in experimental animals (44)(45)(46) . …”
Section: Bioavailability In Ratssupporting
confidence: 80%
“…Similar results were reported from studies on the bioavailability of soybean bound residues of pirimifos methyl (40) , chloropyrofos (41) , dichlorovos (42) and fenitrothion (43) . Also, the data obtained are in line with many other studies which indicate a moderate to high bioavailability of grains bound 14 C-pesticide residues in experimental animals (44)(45)(46) . …”
Section: Bioavailability In Ratssupporting
confidence: 80%
“…The increased serum creatinine and urea levels in deltamethrin-exposed mice agrees with the results of prior studies reporting nephrotoxic changes in workers occupationally exposed to pesticides (El-Gerbed, 2014; Calvert, 2016; Valcke et al, 2017). Treatment of mice with carbofuran and lambda-cyhalothrin has caused elevated blood urea nitrogen and creatinine levels, indicating toxicity to the renal system (Fetoui et al, 2010; Mostafa et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Ram and Singh (1988) have shown biochemical and histopathological changes in liver of Channa punctatus involving cytoplasminolysis, nuclear pyknosis, and necrosis leading to complete exhaustion and disintegration of hepatocytes. Mostafa et al (1992) have shown carbofuran-treated mice have elevated levels of transaminases and blood urea nitrogen indicating toxicity to hepatic structures. In addition, Gupta et al (1994) have reported increase in cholesterol and triglyceride levels after carbofuran exposure in liver.…”
Section: Introductionmentioning
confidence: 98%